Federico and the wolf - Gomez, Rebecca J. (Clarion Books, Houghton Mifflin Harcourt, 2020)
A modern retelling of Little Red Riding Hood in which Federico rides his bicycle to the market for Abuelo's groceries, then stands up to a hungry wolf. Includes a recipe for pico de gallo and glossary of Spanish terms.